The Oceanic Crust - Keen, M. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1975)
Summary I attempt in this article to put in context recent studies of the oceanic crust, studies which led to the drilling of the uppermost few hundred metres of the igneous rocks of the crust on Leg 37 of the Deep Sea Drilling Project. We see that physical measurements - seismic studies, heat-flow measurements and magnetic studies in particular, combined with observations of rocks dredged from the sea floor, and rocks drilled on oceanic islands lead to the idea that the oceanic crust is rather similar to the ophiolite suites seen on land. However, the oceanic crust is altered by the interaction of sea water with hot rocks near the ridge crests, and by cold weathering as the rocks lie exposed to water for millions of years. These alterations affect the physical and chemical properties of the crust, and must play a large part in determining the composition of sea water itself. The thermal processes involved in the rock-sea-water interactions modify the simple model of a cooling plate, where heat transported by the lateral convection of sea-floor spreading is lost by vertical conduction into the oceans.